Investigating The Intentions Of Sustainable EntrepreneurshipAmong Gen Z In The Vision Of The Green Economy In TheMetropolitan Area Of Malang - Alfarizi, Muhammad (PANGRIPTA, 2024)
Sustainable entrepreneurship is vital in today's business landscape, particularly concerning social and environmental responsibility. This study focuses on Generation Z entrepreneurs in the Metropolitan Area of Malang, exploring the impact of Sustainable Development Goals (SDGs) education and Green Economy knowledge on their self-efficacy and intention for sustainable entrepreneurship. Surveying 250 respondents, the research identifies significant positive effects of SDGs education and Green Economy knowledge on Generation Z's entrepreneurial aspirations. Additionally, it highlights the moderating roles of information technology infrastructure and local government support in shaping these relationships. The study emphasizes the need for integrating SDGsprinciples and Green Economy education into educational curricula and local economic policies in Malang. It recommends collaborative efforts among businesses, universities, and schools to promote sustainable practices and proposes equalizing technology infrastructure to ensure equitable access to education and entrepreneurial opportunities. Moreover, it underscores the importance of the local government's support in providing resources and networking opportunities for environmentally and socially responsible businesses. Further research is suggested to evaluate the effectiveness of SDGs in preparing Generation Z for entrepreneurship.